ESR1 Mutations Are Not a Common Mechanism of Endocrine Resistance in Patients With Estrogen Receptor–Positive Breast Cancer Treated With Neoadjuvant Aromatase Inhibitor Therapy - Reinert, Tomás; Ramalho, Susana; de Vasconcelos, Vivian Castro Antunes; Silva, Leonardo Roberto; da Silva, Ana Elisa Ribeiro; de Andrade, Camila Annicchino; Kraft, Maria Beatriz de Paula Leite; Coelho, Guilherme Portela; Mandelli, Jovana; Binotto, Monique; Cabello, Cesar; Paiva Silva, Geisilene Russano de; et al. (Frontiers in Oncology, 2020)
Introduction: Mutations in the ESR1 gene (ESR1m) are important mechanisms of resistance to endocrine therapy in estrogen receptor-positive (ER+) advanced breast cancer and have been recognized as a prognostic biomarker as well as a potential therapeutic target. However, the role of ESR1m as a potential mechanism of primary endocrine resistance as well as whether it also occurs in tumors that are resistant to ET administered in early-stage disease as (neo)adjuvant has not been adequately studied. In this study, we evaluated the prevalence of ESR1m in tumor samples from patients with ER+ breast cancer resistant to neoadjuvant aromatase inhibitor therapy. Methods: We followed a prospective cohort of postmenopausal patients with ER+ HER2- stages II-III breast cancer treated with neoadjuvant endocrine therapy (NET). Tumor samples from patients with a pattern of primary endocrine-resistance (defined as a PEPI score of 4 or more) were identified and analyzed for the presence of ESR1m. Results: One hundred twenty-seven patients were included in the cohort, of which 100 (79%) had completed NET and underwent surgery. Among these patients, the PEPI score ranged from 0 to 3 in 70% (70/100), while 30% (30/100) had a PEPI score of 4 or more. Twenty-three of these patients were included in the analysis. ESR1 mutations were not identified in any of the 23 patients with early-stage ER+ breast cancer resistant to NET. Discussion: Growing evidence supports the notion that there are different mechanisms for primary and secondary endocrine resistance. Our study suggests that ESR1 mutations do not evolve rapidly and do not represent a common mechanism of primary endocrine resistance in the neoadjuvant setting. Therefore, ESR1m should be considered a mechanism of acquired endocrine resistance in the context of advanced disease. Further research should be conducted to identify factors associated with intrinsic resistance to ET.